Patterns of regional economic performance within the context of regional development strategies - Parado, Ma. Rosamund Ramos (Davao City UP in Mindanao, 2008)
This paper examines the effects of regional development strategies on patterns of regional economic performance using joint probability analysis of specialization and concentration patterns and location quotient among the 17 regions of the country from 1990 to 2004. The results indicate that agro-industrialization and the concomitant policy reforms have reinforced the primary of the NCR and the proximal regions in terms of overall regional economic performance over the 14-year period. Conclusions that emerge from these results are threefold. First, patterns of regional specializations are biased towards the services sector. Second, concentration patterns across all sectors are generally dominated by the NCR and the neighboring regions. Third, the development of AAF as an export sector in majority of the regions did not produce the desired forward and backward linkages to the manufacturing sector. Further studies are recommended to explore factors affecting sector concentration and regional specialization patterns, impact of concentration and specialization on the regional economy and dynamics of increase or decrease of location quotients.
Thesis (Urban Regional Planning)--U.P. in Mindanao,2008.
Includes bibliographical references.